FAKTOR PENYEBAB KESULITAN BELAJAR MATEMATIKA DI SEKOLAH DASAR - Nurul Setiani; Uswah; Marvinda Rizki Dita Dirgantara; Rita Suviyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students' understanding of mathematics is still relatively low. Mathematics is often considered a boring and intimidating subject. Many students struggle to understand the material, which then impacts their low learning outcomes. This is partly due to learning methods that focus too much on memorizing formulas. Furthermore, internal and external factors significantly influence mathematics learning. The purpose of this study was to describe the factors causing difficulties in learning mathematics in elementary schools. This study used a qualitative approach with descriptive methods. Qualitative research aims to explore findings, uncover facts and phenomena, variables, and events that occurred during the research process. The results showed that the factors causing difficulties in learning mathematics in elementary schools are both internal and external factors. Therefore, collaboration between teachers, parents, and the school environment is needed to create more effective and enjoyable learning strategies for students. Furthermore, to overcome difficulties in learning mathematics, a comprehensive approach is needed, involving the active role of teachers, parents, and improving the learning environment and strategies to be more engaging, interactive, and tailored to students' needs.